The TGF-beta-Pseudoreceptor BAMBI is strongly expressed in COPD lungs and regulated by nontypeable Haemophilus influenzae - Schultz Holger; Abdullah Mahdi; Röschmann Kristina; Marwitz Sebastian; Ulmer Artur J; Osbahr Sinia; Rohmann Kristina; Rupp Jan; Drömann Daniel; Vollmer Ekkehard; Zabel Peter; Dalhoff Klaus; et al. (Respiratory Research, 2010)
Abstract Background Nontypeable Haemophilus influenzae (NTHI) may play a role as an infectious trigger in the pathogenesis of chronic obstructive pulmonary disease (COPD). Few data are available regarding the influence of acute and persistent infection on tissue remodelling and repair factors such as transforming growth factor (TGF)-β. Methods NTHI infection in lung tissues obtained from COPD patients and controls was studied in vivo and using an in vitro model. Infection experiments were performed with two different clinical isolates. Detection of NTHI was done using in situ hybridization (ISH) in unstimulated and in in vitro infected lung tissue. For characterization of TGF-β signaling molecules a transcriptome array was performed. Expression of the TGF-pseudoreceptor BMP and Activin Membrane-bound Inhibitor (BAMBI) was analyzed using immunohistochemistry (IHC), ISH and PCR. CXC chemokine ligand (CXCL)-8, tumor necrosis factor (TNF)-α and TGF-β expression were evaluated in lung tissue and cell culture using ELISA. Results In 38% of COPD patients infection with NTHI was detected in vivo in contrast to 0% of controls (p < 0.05). Transcriptome arrays showed no significant changes of TGF-β receptors 1 and 2 and Smad-3 expression, whereas a strong expression of BAMBI with upregulation after in vitro infection of COPD lung tissue was demonstrated. BAMBI was expressed ubiquitously on alveolar macrophages (AM) and to a lesser degree on alveolar epithelial cells (AEC). Measurement of cytokine concentrations in lung tissue supernatants revealed a decreased expression of TGF-β (p < 0.05) in combination with a strong proinflammatory response (p < 0.01). Conclusions We show for the first time the expression of the TGF pseudoreceptor BAMBI in the human lung, which is upregulated in response to NTHI infection in COPD lung tissue in vivo and in vitro. The combination of NTHI-mediated induction of proinflammatory cytokines and inhibition of TGF-β expression may influence inflammation induced tissue remodeling.